2007
DOI: 10.1086/511980
|View full text |Cite
|
Sign up to set email alerts
|

Hubble Space TelescopeFine Guidance Sensor Parallaxes of Galactic Cepheid Variable Stars: Period-Luminosity Relations

Abstract: We present new absolute trigonometric parallaxes and relative proper motions for nine Galactic Cepheid variable stars: ℓ Car, ζ Gem, β Dor, W Sgr, X Sgr, Y Sgr, FF Aql, T Vul, and RT Aur. We obtain these results with astrometric data from Fine Guidance Sensor 1r, a white-light interferometer on Hubble Space Telescope. We find absolute parallaxes in milliseconds of arc: ℓ Car, 2.01 ± 0.20 ; ζ Gem, 2.78 ± 0.18 ; β Dor, 3.14 ± 0.16 ; W Sgr, 2.28 ± 0.20 ; X Sgr, 3.00 ± 0.18 ; Y Sgr, 2.13 ± 0.29 ; FF Aql, 2.81 ± 0.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
262
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(299 citation statements)
references
References 60 publications
33
262
4
Order By: Relevance
“…The Cepheid distance is 7.5 ± 0.3 Mpc (Macri et al 2006). In addition, HST trigonometric parallaxes for a sample of Cepheids have become available (Benedict et al 2007), confirming the Key Project period-luminosity calibration, as shown in Figure 25. The probability distribution for H 0 , combining the results of the secondary distance indicators and the full error budget of the Key Project is shown in Figure 26 (Freedman et al 2001).…”
Section: Measurement Of the Hubble Constantsupporting
confidence: 61%
“…The Cepheid distance is 7.5 ± 0.3 Mpc (Macri et al 2006). In addition, HST trigonometric parallaxes for a sample of Cepheids have become available (Benedict et al 2007), confirming the Key Project period-luminosity calibration, as shown in Figure 25. The probability distribution for H 0 , combining the results of the secondary distance indicators and the full error budget of the Key Project is shown in Figure 26 (Freedman et al 2001).…”
Section: Measurement Of the Hubble Constantsupporting
confidence: 61%
“…The recent determination of H 0 = 73.8 ± 2.4 km s −1 Mpc −1 by Riess et al (2011) yields a 1σ uncertainty of only 3.3%, including all identified sources of systematic uncertainty and calibration error. One important change in this analysis is a shift to Cepheid calibration based on the maser distances to NGC 4258 (Herrnstein et al, 1999;Humphreys et al, 2008Humphreys et al, , 2013 and on parallaxes to Galactic Cepheids measured with Hipparcos (van Leeuwen et al, 2007) and with the HST fine-guidance sensors (Benedict et al, 2007). These calibrations circumvent the statistical and systematic uncertainties in the LMC distance, and they directly calibrate the P − L relation in the metallicity range typical of calibrator galaxies, albeit with a sample of only ∼ 10 stars reaching an error-on-the-mean of 2.8% in the case of Milky Way parallaxes.…”
Section: Measurement Of the Hubble Constant At Z ≈mentioning
confidence: 99%
“…Monson et al (2012) calibrate the 3.6µm P − L zero-point against Galactic Cepheid samples, including the Benedict et al (2007) parallax sample, and thereby infer the distance modulus to the LMC as a test of the optical Cepheid P − L relation and its metallicity correction. Freedman et al (2012) use these Milky Way parallaxes to calibrate the optical Cepheid P − L relation and then recalibrate the Key Project data set to infer H 0 ; this determination still relies on optical, WFPC2 Cepheid data (and the associated metallicity corrections and flux and color zero-point uncertainties), and the Key Project SN Ia calibrator sample includes several SNe with photographic photometry or high extinction.…”
Section: Measurement Of the Hubble Constant At Z ≈mentioning
confidence: 99%
“…Hence, we require another constraint, one provided by interferometry. For instance, assuming parallaxes from Hipparcos and HST (van Leeuwen et al 2007;Benedict et al 2007), the radius of Polaris and l Car are 43.5 ± 0.8 and 159.9 ± 16.6 R , respectively Mérand et al 2006). This permits Figure 1.…”
Section: Rates Of Period Changementioning
confidence: 98%